ỨNG DỤNG MẠNG NƠROL TRONG DỰ BÁO ĐỘ LỚN (MAGNITUDE) ĐỘNG ĐẤT KHU VỰC TÂY BẮC VIỆT NAM - Trọng, Cao Đình; Triều, Cao Đình; Vinh, Nguyễn Đức (Vietnam Journal of Earth Sciences, 2011)
The application of Neural Network for Earthquake Magnitude Prediction in Northwest VietnamIn this paper the authors present some primary results of the application of Neural Network for Earthquake Magnitude Prediction in Northwest Vietnam. The following conclusions can be made:- The present Neural Feed Forward yields the best Magnitude Prediction in Northwest Vietnam.- Thanh Hoa 1635M6.7, Dien Bien 1935M6.8, and Tuan Giao 1983M6.7 are the typical earthquakes have been occurred in Northwest in the past.- The large earthquake in Northwest Vietnam can be occurred with the magnitude more than 6.0 in the areas: Son La, Song Ma and Song Ca seismic zones; the overlapped area between Muong Te and Lai Chau seismic zones; and the area from Ha Noi to Hai Phong of Song Hong (Red River) zone.